Efektivitas Perubahan Perilaku dalam Perkara Praktik Penguasaan Pasar dan Penyalahgunaan Posisi Dominan - Pitaloka Alif Savitri; Erna Susanti; Setiyo Utomo (Majelis: Jurnal Hukum Indonesia, 2025)
The rapid growth of Indonesia’s digital economy has created opportunities while simultaneously increasing the risk of monopolistic practices and unfair business competition. To address these issues, the Business Competition Supervisory Commission (KPPU) introduced behavioral remedies as an alternative dispute settlement mechanism. This study aims to analyze the effectiveness of behavioral remedies in cases of market control and abuse of dominant position. The research employs a doctrinal legal method. Effectiveness is assessed through two main indicators, namely the restoration of market conditions and the prevention of repeated violations. The findings show that this mechanism is generally effective in restoring competition and preventing recurrence, as demonstrated in several KPPU cases, including Case No. 04/KPPU-I/2024. However, its effectiveness remains conditional, as the mechanism is reactive, does not impose fines, and is monitored only for a relatively short period. Moreover, although KPPU Regulation No. 2 of 2023 regulates this mechanism, it does not provide sufficient legal explanation regarding the classification of articles that are permitted. Therefore, stronger monitoring and more detailed legal clarification are required to ensure the sustainable effectiveness of this mechanism in maintaining fair competition.